The Cognitive-Enhancing Effects of Dendrobium nobile Lindl Extract in Sleep Deprivation-Induced Amnesic Mice - Jiang, Ning; Li, Yu-jiao; Wang, Meng-di; Huang, Hong; Chen, Shanguang; Li, Yinghui; Qu, Lina; Wang, Fengzhong; Liu, Xinmin; Wang, Qiong (Frontiers in Psychiatry, 2022)
Chronic sleep deprivation (SD) causes neurological and neurodegenerative dysfunction including learning and memory deficit. The orchid Dendrobium nobile Lindl (DNL), is widely used as a Yin tonic and medicinal food throughout Asia, and has many reported pharmacological effects. This study focused on the cognitive-enhancing effects of DNL in sleep deprivation-induced amnesia in mice and its biochemical mechanisms. Our results showed that the mice displayed significant cognitive deficits after 2-week SD while treatment with the extract of DNL prevented these impairments. In the novel object recognition and object location recognition tasks, a significant increase in the discrimination index was observed in DNL-treated (200 and 400 mg/kg) mice. In the MWM test, DNL (200 and 400 mg/kg) treatment shorten the prolongation of latency and increased the crossing numbers compared with SD mice. The biochemical analysis of brain tissue showed a decrease in NE, dismutase (T-SOD) and catalase (CAT) activity and an increase in 5-HT and malondialdehyde (MDA) concentration after the treatment with DNL in mice. Our findings indicated that DNL exerted a positive effect in preventing and improving cognitive impairment induced by SD, which may be mediated via the regulation of neurotransmitters and alleviation of oxidative stress.